Called out of darkness : [compact disc, unabridged] : a spiritual confession - Rice, Anne, 1941- (Random House Audio, 2008)
Anne Rice's intimate memoir of her Catholic girlhood explores her unmaking as a devout believer and the path she found to a new belief in her faith.